Criminal Liability in Corporate Governance: A Study of White-Collar Crimes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The criminal justice system is facing a growing number of instances of corporate misbehavior in the twenty-first century. In order to maximize their own personal gain, some entrenched interests that dominate corporate operations utilize the corporation to commit illegal crimes. Companies are granted legal existence so they may be governed by the law. However, it becomes difficult to hold a corporate body criminally accountable due to the absence of a physical body and mind in a corporate organization. Damage to ecosystems, human health, and the advancement of necessary infrastructure may result from unethical business practices. In today's criminal justice system, it is essential to properly formulate criminal justice activities and to effectively enforce corporate criminal responsibilities. Freedom of commerce, a friendly business climate, and little regulation of corporate organizations are crucial to the economic well-being of society, the prosperity of citizens, and the growth of nations. In order to improve society via the determination and enforcement of corporate criminal culpability, it is vital to strike a balance between being tough on corporate crimes and being careful not to impede legitimate business activity. This presentation will provide an analysis of the Indian law concerning corporate criminal responsibility.